Arranjos produtivos locais: calçados femininos de Jaú e Santa Cruz do Rio Pardo - Alves, Paulo Roberto (2014)
This work aims at providing a comparative analysis of the case studies of two clusters producers of women's footwear, both located in the central region of the state of São Paulo: Jaú and Santa Cruz do Rio Pardo. These objects of study were suggested by the Departamento de Competitividade e Tecnologia da Federação das Indústrias do Estado de São Paulo - DECOMTEC/FIESP (Department of Competitiveness and Technology of the Federation of Industries of the State of São Paulo) and are both in the same industry sector, having similar industrial maturity and being distant from the Metropolitan Region of São Paulo. The cluster of Jaú, larger, more structured and with it s own governance, receives government incentives; on the other hand, the cluster of Santa Cruz do Rio Pardo, smaller, less structured and without it s own governance, doesn t. The research studied whether agglomerations encouraged by the government, directly or indirectly, can spread economic and social benefits to society, and also intended to identify these benefits, quantifying them, and comparing them with those which the concentration that receives no incentives provides. The existing literature highlighted the economic externalities of productive concentrations - this thesis, in an unprecedented way, looks at their social side and seeks to identify the social and economic externalities they bring. The conclusions point to the fact that the two concentrations still lack a strong structuring and more involvement, besides support institutions, particularly from the government, but they also show that the social and economic externalities of both clusters are very intense in the cities and regions that where these clusters are hosted